Aspectos clínicos e laboratoriais de doenças víricas, parasitológicas e bacterianas que acometem cães - Mortari, Ana Paula Gnocato (2023)
Infectious diseases of dogs are caused by several viral, bacterial and parasitic pathogens. Many of these agents have worldwide distribution and rapid spread, and can also be transmitted to humans, significantly impacting public health. Many agents cause similar clinical signs that make diagnosis difficult and, although it is often not investigated, the occurrence of co-infections is common, which can worsen the clinical picture and make the treatment of affected animals difficult. In addition, dogs are considered reservoirs and important epidemiological indicators of several diseases. Therefore, the objective of this thesis was to investigate the occurrence of protozoan, viral and bacterial infections and co-infections of dogs in southern Brazil, as well as to determine the seroprevalence for Toxoplasma gondii in the dog population of Santa Maria.In chapter 1, we report a natural Trypanosoma cruzi infection in a 2-month-old dog with apathy, anorexia, diarrhea, paleness of mucous membranes and hypoglycemia from a kennel in Porto Alegre. The blood smear showed alterations compatible with Trypanosoma spp. infection and T. cruzi DNA was detected by PCR in the myocardium. Evidencing the importance of veterinary doctors' knowledge about T. cruzi infection in dogs in the region, and the potential role of dogs as reservoirs of this parasite for humans. In chapter 2, we analyzed the frequency of detection of anti-T.gondii antibodies in the serum of dogs from Santa Maria, before and after the outbreak of toxoplasmosis in humans that occurred in 2018, by the indirect immunofluorescence technique (IFAT). We noticed an increase in seroprevalence after the outbreak, indicating that dogs were also affected in the outbreak, probably due to the ingestion of contaminated water, as occurred in the human population. Chapter 3 describes the coinfection of canine circovirus (CanineCV) and canine distemper virus (CDV) in a 3-month-old dog with pathological lesions compatible with CDV-induced disease in southern Brazil. Thus, we verified the presence of CanineCV in viral co-infections in multisystemic diseases and highlighted its circulation in dogs in Brazil. And in chapter 4, we describe the clinical and laboratory findings of single and mixed infections in stool and intestinal fragment samples from 76 dogs from southern Brazil with a history of severe enteritis. Through histopathology and molecular testing, Carnivore protoparvovirus 1 (CPV) was the pathogen most frequently detected in both single and mixed infections, followed by Giardia sp., Cryptosporidium spp., and Clostridium perfringens A. Demonstrating the diversity of microorganisms involved in intestinal infections of dogs in southern Brazil, especially in co-infections. Together, these four works highlight the importance of investing in laboratory tests to obtain a definitive diagnosis of infectious diseases in dogs, and demonstrate the main infectious agents that are circulating in these animals in southern Brazil. Thus, the results of this thesis can contribute to the diagnosis and planning of control measures for important infectious diseases of dogs in the study region, as well as agents with zoonotic potential.